WITHDRAWN Soft Chemical Synthesis of Nickel-Zinc-Cobalt-Ferrite Nanoparticles and their Structural, Morphological and Magnetic Study at Room Temperature (Journal of Nepal Physical Society, 2021)
This article was withdrawn on 7th April 2025.The withdrawal was carried out at the request of the journal’s editor and the corresponding author.